L’image faite corps. Dix figures sur la pratique du tableau vivant au Québec avant 1920 - Lacroix, Laurier (RACAR : Revue d'art canadienne / Canadian Art Review, 2019)
A significant number of cultural practices in New France and Canada originate in the colonial situation and echo French and British art forms. This article focuses on the early use of the tableau vivant in Quebec, from its first reference in 1641 to the early twentieth century, in family and public entertainment, celebrations and pageants, educational and artistic manifestations. The tableau vivant thus presented itself as both popular and erudite art. In order for this art form to function, certain works needed to be present in the collective imaginary and shared culture; performers needed to master the content of the re-presented image and spectators needed to recognize it and to appreciate the efforts expended to embody it. This article briefly examines the history of the tableau vivant in Europe in order to identify the stages of its development in Quebec.